Analysis of Factors Influencing Academic Achievement of Working Students - Yustika, Wida; Harahap, Isnaini; Aisyah, Siti (International Journal of Multidisciplinary Research of Higher Education, 2025)
This study addresses the increasing prevalence of burnout among working university students, a condition that threatens both their psychological well-being and academic success. Although previous research has explored the link between burnout, emotional intelligence, and performance, limited evidence exists in the context of higher education students who balance dual roles in developing countries. The present study aims to analyze the effect of burnout on the academic performance of working students, with emotional intelligence positioned as a mediating variable. A quantitative approach with an explanatory design was employed, involving 300 undergraduate students from private universities in North Sumatra, Indonesia, who simultaneously study and work. Data were collected using validated instruments and analyzed through Structural Equation Modeling with the Partial Least Squares method. The findings reveal that burnout significantly and negatively affects both emotional intelligence (β = –0.670, p < 0.001) and academic performance (β = –0.268, p < 0.001). Emotional intelligence exerts a positive effect on academic performance (β = 0.188, p = 0.007) and significantly mediates the relationship between burnout and performance (β = –0.126, p = 0.008). These results confirm the protective role of emotional intelligence in reducing the detrimental effects of burnout and highlight its importance in sustaining students’ academic achievement. The study contributes to theoretical advancement in burnout and emotional intelligence research while offering practical implications for higher education institutions to develop emotional regulation programs that support the resilience of working students.